FORGING DIPLOMATIC BRIDGES: EXPLORING THE ROLE OF TÜRKIYE SCHOLARSHIPS IN STRENGTHENING THE RELATIONSHIP BETWEEN INDONESIAN GRADUATES AND TURKIYE - Rosadi, Raesita Rakhmawati; Sayimer, Idil; Wiradharma, Gunawan (Srawung: Journal of Social Sciences and Humanities, 2025)
This research addresses the growing importance of soft power in international relations, particularly through educational initiatives like the Türkiye Scholarships. The problem statement highlights the need for effective public diplomacy tools that can foster enduring connections between nations, specifically between Turkey and Indonesia. The Turkish Scholarship program is positioned as a strategic effort to enhance Turkey's influence and strengthen bilateral relations through cultural and educational exchanges. The purpose of this research is to explore the role of Indonesian graduates from the Türkiye Scholarships in promoting Turkey's soft power and public diplomacy within Indonesia. By focusing on these alumni, it aims to understand how their experiences in Turkey have influenced their professional lives and their contributions to fostering positive perceptions of Turkey in their home country. This research employs a qualitative methodology, utilizing a case study approach. Data was collected through in-depth interviews with six Indonesian graduates working in various sectors of the Indonesian government, including banks, ministries, and universities. The interviews were conducted between September and October 2022, allowing for a comprehensive analysis of the graduates' experiences and their impact on Turkey's diplomatic efforts. The findings reveal that Indonesian graduates of the Türkiye Scholarships have successfully integrated Turkish values into their careers and daily lives, serving as informal ambassadors for Turkey. Their positions in key governmental roles signify a significant soft power investment for Turkey, as they actively contribute to projects and collaborations that enhance bilateral relations.